Anemia in Pregnant Women and Mothers Education Level as Risk Factor for Stunting in Children Aged 24-59 Months - Zainury, Muchamad Iqbal; Dasuki, Mohammad Shoim; Basuki, Sri Wahyu; Lestari, Nining (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Stunting is one of the nutritional problems that can occur in toddlers which can be caused by various factors such as anemia in pregnant women and the level of education of mothers. The prevalence of stunting globally reaches 22%. Indonesia itself has a stunting percentage of 27.7% in 2019, 26.9% in 2020 and 24.4% in 2021 despite the decline, but it is still far from the desired target of 14% in 2024. This study aims to analyze the relationship between anemia in pregnant women and the level of maternal education with the incidence of stunting in children under the age of 24-59 months. This type of research uses observational analytics, with a case control design. The size of the sample used was 142 samples, purposive sampling, and data collection using secondary data obtained at the Bandarharjo Health Center. Data were obtained from maternal cohort books, maternal and child health (MCH) books, medical records, and e- PPGBM (electronic-Community-Based Nutrition Recording and Reporting). The results of this study obtained the children of the respondents, namely 56.3% more women than 43.7% of men. From the chisquare test results, a p value = 0.013 was obtained in the anemia variable in pregnant women (OR = 2.46) and the level of maternal education p = 0.001 (OR = 3.25) for stunting events. The results of the logistic regression test obtained an OR anemia value in pregnant women of 2.46, while the maternal education level was 3.25. In conclusion, there is a significant relationship between anemia in pregnant women and the level of maternal education with the incidence of stunting.